Real-Time Adaptive VVO/CVR Topology Using Multi-Agent System and IEC 61850-Based Communication Protocol - Manbachi, Moein; Nasri, Maryam; Shahabi, Babak; Farhangi, Hassan; Palizban, Ali; Arzanpour, Siamak; Moallem, Mehrdad; Lee, Daniel C. (IEEE transactions on sustainable energy, 2014)
This paper proposes a new approach for real-time and adaptive Volt/VAr optimization (VVO)/conservation voltage reduction (CVR) system using Intelligent Agents, communicating through IEC 61850 Goose Messaging Protocol. The paper also proposes new real-time adaptive VVO/CVR algorithms tailored for different service level targets and system topologies. The paper argues that each of these variations requires different Intelligent Agent Systems, data structures, and communication requirements. To test the applicability of the VVO/CVR optimization engine, a modified IEEE 34 Node system is used as case study.